Evolution law of stress induced by pressure depletion in fractured shale reservoirs: Implications for subsequent refracturing and infill well development - Qiang Wang; Yufeng Wang; Rong Wang; Jinzhou Zhao; Yongquan Hu; Jin Zhao (Petroleum)
Stress changes associated with reservoir depletion have been frequently observed. Stress evolution within and around the drainage areas can affect the completion of infill wells and refracturing considerably. To accurately predict the stress distribution in shale gas reservoirs, a coupled fluid-flow/geomechanics model considering the microscopic seepage mechanism of shale gas and the distribution of complex natural fractures (NFs) was derived based on Biot's theory, the embedded discrete fracture model, and the finite volume method. Based on this model, stress can be predicted by considering the mechanisms of adsorption, desorption, diffusion, and slippage of shale gas and the random distribution of NFs. The results show that in the process of stress evolution, there will be extremes of σxx, σyy, σxy, Δσ, α, and stress reversal area at a certain point, and the time of occurrence of extremes differs at different positions. The key to determining this law is the pore pressure gradient, with a spatiotemporal evolution effect. Different microscopic seepage mechanisms significantly influence the storage and transmission of shale gas, leading to significant differences in the distributions of reservoir pressure and stress. The larger the initial stress difference, the more difficult the stress reversal. When the initial stress difference exceeds a certain limit, stress reversal does not occur in the reservoir. Under the influence of the distribution difference of the NFs, the shape of the pressure-depletion area and magnitude of the pressure gradient differed significantly. As the approaching angle of NFs increased, the range of stress reversal in the top and bottom parts of the domain gradually decreases; At the same time, the orientation of maximum horizontal stress (MHS) near the fractures also gradually decreases. When the approaching angles of the NFs are the same, the number of natural fractures has little effect on the stress. Owing to the effect of NFs and hydraulic fracture, the anisotropy of stress is enhanced, the occurrence time of extreme value of local stress and stress reversal area differ significantly, and selecting the timing of infill well fracturing and refracturing becomes difficult. This research is essential to understanding the stress evolution law of shale gas reservoirs and guiding the completion of infill wells and refracturing design.